Rapid dynamic activation of a marine‐based Arctic ice cap. Issue 24 (23rd December 2014) - McMillan, Malcolm; Shepherd, Andrew; Gourmelen, Noel; Dehecq, Amaury; Leeson, Amber; Ridout, Andrew; Flament, Thomas; Hogg, Anna; Gilbert, Lin; Benham, Toby; van den Broeke, Michiel; Dowdeswell, Julian A.; et al.
Abstract We use satellite observations to document rapid acceleration and ice loss from a formerly slow‐flowing, marine‐based sector of Austfonna, the largest ice cap in the Eurasian Arctic. During the past two decades, the sector ice discharge has increased 45‐fold, the velocity regime has switched from predominantly slow (~ 101 m/yr) to fast (~ 103 m/yr) flow, and rates of ice thinning have exceeded 25 m/yr. At the time of widespread dynamic activation, parts of the terminus may have been near floatation. Subsequently, the imbalance has propagated 50 km inland to within 8 km of the ice cap summit. Our observations demonstrate the ability of slow‐flowing ice to mobilize and quickly transmit the dynamic imbalance inland; a process that we show has initiated rapid ice loss to the ocean and redistribution of ice mass to locations more susceptible to melt, yet which remains poorly understood.